Comparison of control methods of cucumber green mottle mosaic virus disease and their prospects - XIE Ting; LUO Jinyan; CHEN Lei; DU Wei; ZHU Jie; LI Bin (浙江大学学报. 农业与生命科学版, 2022)
Cucumber green mottle mosaic virus (CGMMV) is widely distributed in the world. It mainly infects cucurbitaceous crops, causing serious damage and incalculable economic loss to the commercial planting and production of cucurbitaceous crops. This paper analyzed the main factors affecting the rapid spread and epidemic of CGMMV, summarized the prevention and control strategies of CGMMV in epidemic areas focusing on seed disinfection and non-epidemic areas focusing on prevention of transmission, introduced the main detection methods of CGMMV, such as serology and molecular biology, compared the advantages and disadvantages of various existing control methods, and looked forward to the application prospect of new antiviral agents and genetic engineering technologies in the control of CGMMV.